A STUDY OF THE FIRST-YEAR STUDENTS PERCEPTIONS REGARDING THE STRATEGY OF IIB DARMAJAYA’S MARKETING COMMUNICATION APPROACH DURING COVID-19 PANDEMIC - Novita Sari; Firmansyah Yuni Alfi; Winni Sari (Prosiding International conference on Information Technology and Business (ICITB), 2020)
Covid-19 has brought some negative impact globally, including the declining interest to register in universities due to economic unaffordability. This study will obtain information about how students perceive Darmajaya in the middle of this Covid-19 spread. For the marketing area, this information might give an additional strategy on how to attract new students in a new different way in increasing the number of total new admissions. This study used the approach of qualitative phenomenological study. To acquire the data, the researcher used the deep-interview method. A sample of 14 students of Darmajaya’s first year-students and a number of selection criteria were identified. From the informants, it was obtained that Darmajaya had built a good perception among the students regarding the service quality, accreditation, lecturers’ quality, achievements, web, and social media accessibilities as well as popular events and competitions but it needed an improvement in scholarship socialization, needed to expose more of the students’ organizations (UKM) in social media and needed to enrich the major/courses in order to attract the new enrollers to register.Keyword: Students, Education, Pandemic Covid 19, Perceptions, Marketing strategy